1992
DOI: 10.1007/bf00384720
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of autotransplanted splenic tissue at different implantation sites

Abstract: Inbred animals (Lewis rats) were used to investigate the regeneration of autologously implanted splenic tissue at intra-omental and subcutaneous sites. Quantitative immunohistology with monoclonal antibodies against lymphocytes and macrophages was performed to analyse the cell density of red pulp (RP), periarteriolar lymphoid sheath (PALS), marginal zone (MZ) and follicle, 7-180 days after transplantation. Antigenic, allogeneic and mitogenic stimulation and Northern blotting were also performed. Transplant gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Our data are in accord with studies in which normal numbers of IgM PFCs were detected 3 to 4 months after splenic implantation in both omental and subcutaneous transplants in rats 19 . Consistent with this assumption, a restored serum antibody response to intravenous challenge with SRBCs was described after intraperitoneal and subcutaneous splenic autotransplantation, with no rise in the asplenic animals 27 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data are in accord with studies in which normal numbers of IgM PFCs were detected 3 to 4 months after splenic implantation in both omental and subcutaneous transplants in rats 19 . Consistent with this assumption, a restored serum antibody response to intravenous challenge with SRBCs was described after intraperitoneal and subcutaneous splenic autotransplantation, with no rise in the asplenic animals 27 .…”
Section: Discussionsupporting
confidence: 91%
“…We cannot formally exclude the possibility that the suture thread used for the intraomental implants contributed to the complications in this scenario. Furthermore, in the case of the omentum autotransplant site, torsion of the omentum has been described as a cause of acute abdomen 11,19 and aseptic necrosis of the graft 29 . We suspect that the same type of adhesions observed in our model could occur in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of studies have confirmed morphological regeneration of autotransplanted splenic tissue [32][33][34][35]. However, splenic regeneration does not necessarily mean recovery of organ function.…”
Section: Discussionmentioning
confidence: 99%
“…Various implantation sites have been described, including subcutaneous tissue, the retroperitoneum, muscles of the abdomen, and the greater omentum. The greater omentum implantation site is the most widely used and also the most recognized in the literature (9). No significant differences have been found between the splenic implants located in the greater omentum and other intraperitoneal sites regarding their morphology and capacity to produce antibodies (5).…”
mentioning
confidence: 99%